Eternity in their hearts - Richardson, Don, 1935-2018 (Ventura, Calif. : Regal Books, 2005)
Has the God who prepared the gospel for all people groups also prepared all people groups for the gospel? Don Richardson, author of the best-selling book Peace Child, has studied cultures throughout the world and found within hundreds of them startling evidence of belief in the one true God. In Eternity in Their Hearts, Richardson gives fascinating, real-life examples of ways people have exhibited in their histories terms and concepts that have prepared them for the gospel. Read how Pachacuti, the Inca king who founded Machu Picchu, the majestic fortress in Peru, accomplished something far more significant than merely building fortresses, temples or monuments. He sought, reached out and found a God far greater than anypopulargod of his own culture. And there have been others throughout the world, like him, who lived to receive the blessing of the gospel. Get ready to be amazed at these intriguing examples of how God uses redemptive analogies to bring all men to Himself, bearing out the truth from Ecclesiastes that God has also set eternity in the hearts of men. - Publisher.
Part one. A world prepared for the gospel : the Melchizedek factor. Peoples of the vague God -- Peoples of the lost book -- Peoples with strange customs -- Scholars with strange theories -- Part two. The gospel prepared for the world : the Abraham factor. The 4,000-year connection -- A Messiah for all peoples -- The hidden message of Acts -- Author's postscript -- Questions for study.
Bibliography: p. [202]-205.
Keywords: Jesus Christ -- Miscellanea; Religion